2019
DOI: 10.2174/1381612825666190709220449
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Patients Receiving New Anticoagulants

Abstract: There is an increased use of oral anticoagulants for the prevention of venous and arterial thrombosis. Vitamin-K antagonists have been used for decades as the main oral anticoagulants but they have the draback a complex therapeutic management, slow onset of action and by a different oral intake caused by dietary vitamin K intake. New non-vitamin K antagonist oral anticoagulants (NOACs) have been developed to overcome the limitations of warfarin. Their management is easier as it requires a fixed daily dose with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The optimal time of DOAC discontinuation before surgery has not been established, particularly in patients with kidney failure. 2 Reversal agents for DOACs remain expensive and rare and, as with DOACs, the safety and efficacy of these agents in the kidney failure population is lacking. Although table 2 of the De Vriese et al manuscript notes one trial participant who discontinued rivaroxaban prematurely due to "registration on the transplant list," the authors do not report how many other subjects were already on a transplant waiting list.…”
Section: Addressing Transplant Candidacy When Evaluating Safety Of Di...mentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal time of DOAC discontinuation before surgery has not been established, particularly in patients with kidney failure. 2 Reversal agents for DOACs remain expensive and rare and, as with DOACs, the safety and efficacy of these agents in the kidney failure population is lacking. Although table 2 of the De Vriese et al manuscript notes one trial participant who discontinued rivaroxaban prematurely due to "registration on the transplant list," the authors do not report how many other subjects were already on a transplant waiting list.…”
Section: Addressing Transplant Candidacy When Evaluating Safety Of Di...mentioning
confidence: 99%
“…Alternatively, prothrombin complex concentrates can be used, despite not being specific reversal therapy agents, but published experience at the time of emergency surgery is limited to case reports. 2 A survey of reversal practices among adult transplant programs in the United States indeed revealed that, although 64% of kidney transplant programs allow patients to remain on direct oral anticoagulants (DOAC) while on the transplant waiting list, only 7.8% reported routine use of DOAC reversal agents. 3 This large practice variability calls for more guidance by professional societies, pending reliable research in this context.…”
Section: Authors' Replymentioning
confidence: 99%
See 1 more Smart Citation
“…Heparinoid bridging for anticoagulation "Bridging" is the act of administering short-acting and reversible anticoagulants while OAT is interrupted, and the international normalized ratio (INR) is subtherapeutic. This provides the patient with TE protection until the patient is safely transitioned back on to OAT within the therapeutic range (Douketis & Lip, 2019).…”
Section: Definitionsmentioning
confidence: 99%